HPB P55 Procedure Specific Consent Forms for Laparoscopic Cholecystectomy. (7th December 2022) - Manson, David; McKnight, Gerard; Johnston, Meabh; O'Reilly, David; Alessandri, Giorgio
Abstract: Background: Surgical consent forms can be difficult for patients to read and understand. Important points including procedure details, relevant complications and alterative treatment options are often lost in the communication process. Furthermore, surveys have found that patients struggle to grasp basic surgical concepts. Procedure specific consent forms (PSCFs) have been shown to improve the process of surgical consent. This is partly because they provide a standardised list of complications and their incidence, presented in a uniform, legible format without any abbreviations. However, despite their benefits, PSCFs are nationally underused. Cholecystectomy is one of the most common operations performed in the United Kingdom. Due to the pandemic disrupting elective surgical lists, the backlog of patients with biliary pathology has increased. More patients are therefore presenting to the on-call surgical team with biliary disease. Many trusts employ an Emergency Surgery Ambulatory Care (ESAC) list to offload the stretched emergency service. Our aim was to assess the variability of cholecystectomy consent forms amongst this cohort of patients, subsequently review patient understanding and evaluate whether the introduction of a procedure specific consent form improved this understanding. Methods: We performed a prospective audit of laparoscopic cholecystectomy consent forms using the ESAC service. These consent forms were all obtained from patient's paper notes and assessed individually for variables. The first loop of the audit assessed the consent form used for the first 20 patients allocated to the ESAC list. Subsequently, each patient was telephoned post-operatively and asked a series of standardised questions which were adapted from a published questionnaire. Following this, we introduced a Procedure Specific Consent Form (PCSF) for laparoscopic cholecystectomies, with the agreement of all consultant surgeons who perform this operation in the trust. The second loop of the audit assessed another 20 patients from the emergency list, after the introduction of the PCSF. Similarly, patients were later telephoned to assess understanding. Over both loops, each consent form was assessed for the scope of their included complications and measured against the NHS-recognised list of potential adverse outcomes. Secondly, the legibility of the consenter's writing and the use of any abbreviations was noted. Legibility was evaluated by two doctors independently to reduce subjectivity. Results: The first loop revealed that all forms contained infection and bleeding; 90% included injury to bile duct ; 80% included injury to viscera and risks from general anaesthetic ; 75% included blood clots and bile leak ; and only 55% included post-cholecystectomy syndrome . The additional complications included were pain, herniae, covid risk, retained stone, collection, pancreatitis, failure and death ; with an even higher degree of variability. The 20 forms were 95% legible, with 50% of them containing one or more acronyms. Relating to the post-op questionnaire, >80% of patients remembered details surrounding their operation, however only 60% could recall basic potential complications. After PCSF introduction, it was used in 10 of the second loop cases, with the remaining 10 using traditional Consent Form 1 (non-PSCF). The non-PSCF group demonstrated similar variability in the complications included, with identical legibility rates and acronym usage. Again, only 60% of patients were able to accurately define the associated complications. Of the PSCFs, 100% were legible and 0% used acronyms, and the list of complications was standardised with 100% compliance with NICE and RCS England guidance. Notably, 90% of patients accurately recalled potential complications and nearly all were satisfied with their level of understanding prior to signing the consent form. Conclusions: This Quality Improvement Project demonstrated that hand written Consent Forms are highly variable, especially regarding the list of complications. We also found that while they were largely legible, half of the consent forms contained acronyms. Lastly, patients were satisfied with the information provided to them and could recall knowledge on the nature of the surgery, but many were not able to recollect important potential complications. The use of a PSCF allowed for a standardised, easily accessible, legible consent form devoid of misinterpretable acronyms. This was reflected in the patient questionnaire, where patients were able to recall details of the surgery and were satisfied with their level of understanding. This was reaffirmed by their grasp of the complications, where 90% of patients could recall potential adverse risks, compared to 60% in the Form 1 groups. This audit demonstrates the benefit of PSCFs from a legislative and litigative standpoint, but more importantly from the standpoint of patient understanding and holistic care. We recommend the use of PSCFs in the process of all surgical consent, to help ensure patient understanding and subsequent satisfaction.